Circular RNA HIPK3 induces cell proliferation and inhibits apoptosis in non-small cell lung cancer through sponging miR-149. Issue 2 (1st February 2020) - Lu, Huibin; Han, Xinwei; Ren, Jianzhuang; Ren, Kewei; Li, Zongming; Sun, Zhanguo
ABSTRACT: Circular RNAs (circRNAs) are a class of endogenous noncoding RNAs that are demonstrated to be potent regulators in the development of various types of human cancers, including non-small cell lung cancer (NSCLC). In the present study, the level of circRNA-HIPK3 were measured by Taq-man based quantitative real-time PCR (qRT-PCR) analysis in both NSCLC patient specimens and cells, which showed that circRNA-HIPK3 was upregulated in both NSCLC tissues and cell lines. Cell counting kit-8 (CCK-8), migration and flow-cytometry assays indicated that circRNA-HIPK3 participated in the regulation of the proliferation, migration, invasion and apoptosis of NSCLC cells. MiR-193a expression was increased by circHIPK3 silencing. We then showed that miR-149 interacts with FOXM1 by binding to the 3ʹ-untranslated region (UTR). Further, ectopic overexpression of miR-149 by transfecting miR-149 mimics significantly inhibited growth, migration and invasion of HSCLCs, which was found to be mediated through FOXM1. Moreover, miR-149 overexpression decreases the viability and proliferation of HSCLCs. Therefore, our data suggest that circHIPK3 regulates the function of NSCLCs through miR-149-mediated FOXM1 expression regulation, potentially providing a novel insight into the pathogenesis of NSCLC.